Differentiation of Promonocytic U937 Cells to Monocytes Is Associated with Reduced Mitochondrial Transport of Ascorbic Acid. (8th February 2018) - Scotti, Maddalena; Fiorani, Mara; Guidarelli, Andrea; Cantoni, Orazio
Abstract : Growth of promonocytic U937 cells in the presence of DMSO promotes their differentiation to monocytes. After 4 days of culture in differentiating medium, these cells ceased to proliferate, displayed downregulated ryanodine receptor expression, and responded to specific stimuli with enhanced NADPH-oxidase-derived superoxide formation or cytosolic phospholipase A2 -dependent arachidonic acid release. We found that the 4-day differentiation process is also associated with downregulated SVCT2 mRNA expression, in the absence of apparent changes in SVCT2 protein expression and transport rate of ascorbic acid (AA). Interestingly, under the same conditions, these cells accumulated lower amounts of the vitamin in their mitochondria, with an ensuing reduced response to external stimuli sensitive to the mitochondrial fraction of AA. Further analyses demonstrated an unexpected increase in mitochondrial SVCT2 protein expression, however, associated with reduced SVCT2-dependent AA uptake in isolated mitochondria. A decrease in the transporter Vmax, with no change in affinity, was found to account for this response. Differentiation of promonocytic cells to monocytes is therefore characterized by decreased SVCT2 mRNA expression that, even prior to the onset of SVCT2 protein downregulation or apparent changes in plasma membrane transport activity, impacts on the mitochondrial accumulation of the vitamin through a decreased Vmax of the transporter.